Peran Teknologi Informasi dalam Meningkatkan Efektivitas Administrasi Publik di Indonesia - Agni Afdilati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the role of information technology in improving the effectiveness of public administration in Indonesia. Using a descriptive qualitative approach, this research highlights how technology supports administrative simplification, transparency, and responsiveness to public needs. The study finds that national platforms such as SP4N-LAPOR!, OSS-RBA, and SIPD have contributed to reducing bureaucratic barriers and enhancing public service quality. However, challenges such as digital literacy gaps and infrastructure inequality persist, requiring continuous improvement strategies. The conclusion emphasizes that adaptive policies and human resource capacity development are key to maximizing the benefits of technology in public administration.